Systematic Literature Review: How to Increase Milk Production in Breastfeeding Mother - Laili, Fitria Jannatul (JURNAL KEBIDANAN BESTARI, 2021)
The most common reason cause of exclusive breastfeeding failure is the assumption of insufficient breast milk of breastfeeding mothers. The aim of this systematic review is to know how to increase milk production in breastfeeding mothers. This study followed the PRISMA guidelines for systematic reviews, a literature search was carried out to assess articles that explain how to increase milk production in breastfeeding mothers. Consume herbal ingredients and massage, acupressure, hypno-breastfeeding as a combination method can help mothers to increase milk production. Midwives can promote combine method to improve milk production in breastfeeding mothers. Keywords: Milk Production, Breastfeeding Mother